MON-034 Novel Estrogen Activity and Gene Regulation Induced by Personal Care Products in Breast Cancer Cells - Crease, Keturah (J Endocr Soc, 2019)
The contribution of personal care product (PCP) use to hormone regulated cancer and cancer disparities is unknown. Considering that environmental estrogens and endocrine disrupting chemicals (EDCs) have the potential to contribute to cancer promotion and progression, evaluating chronic use PCPs and hair products for estrogen activity may be of use for risk assessment. In this study, we tested the hypothesis that the ethanol extracts of 11 PCPs (including hair products) would induce estrogen agonist or antagonist activity in breast cancer cells in culture. We have previously shown that three of these PCP extracts induce estrogen agonist activity in the MCF-7 E3 estrogen proliferation assay while six extracts induce estrogen antagonist effects in the T47dkbluc estrogen reporter gene assay. In the current study, the LanthaScreen TR-FRET ER Alpha Competitive Binding Assay was employed to confirm that all nine estrogenic PCP extracts bind to the ER with up to 85% of the activity of E2. Then, to compare endogenous gene regulation induced by the estrogenic PCP extracts with treatment with E2, the Qiagen RT2 Profiler PCR Array for Human Estrogen Receptor Signalling was utilized. MCF-7 cells were treated with solvent control, 1 nM E2 or one of the nine PCP extracts shown to have estrogen activity in bioassays. The three extracts with agonist activity in bioassays produced a gene activation pattern similar to E2 with fewer total genes induced. At the same time, these extracts had no effect on some genes E2 inhibited (compared to control). While the extracts with estrogen antagonist activity in the bioassays inhibited the transcription of most genes induced by E2, these extracts activated the transcription of a number of genes E2 either down regulated or did not regulate. The antagonist PCP extracts repressed transcription of as many as 20 genes such as GPER1, PGR, NR5A2, CAV1 relative to E2. At the same time, in contrast to E2, these extracts induced the transcription of genes such as CYP1A1, CKB, CTGF, WNT4, CTGF, S100A6, FST, NCOA1 CTGF, S100A6, FST, NCOA1, APBB1, PTCH1, MAFF, WNT5A, and/or NOV. We conclude that chronic exposure to these estrogenic or antiestrogenic PCPs has the potential to impact estrogen mediated signaling in exposed individuals that exposure may have an influence on the proliferation and survival of estrogen dependent cancer.